Integrating Indigenous Knowledge into Sustainable Forest Management for Climate Change Adaptation and Mitigation Strategies: Case from Southern Slopes of Mount Slamet, Indonesia - Budiman, Mokhamad Asyief Khasan; Oue, Hiroki (Jurnal Manajemen Hutan Tropika, 2025)
Frequent natural disasters and extreme weather increase the vulnerability to climate change in rural communities living near forests. Climate change adaptation and mitigation strategies related to forest management should consider indigenous knowledge in accordance with local community conditions and needs. This study aimed to investigate the indigenous knowledge of forest management to cope with climate change challenges. The research was conducted in April - May 2024 in the southern slopes of Mount Slamet, Central Java (i.e., Gununglurah, Sokawera, and Sunyalangu Villages). The research approach uses Participatory Learning Action with descriptive-quantitative analysis based on interpretive and critical sociology. This study revealed that indigenous knowledge comprises three types of forest management. Firstly, the community categorized the forest into three types of space: sacred conservation forests (Tabet), protected forests in steep areas, and production forests using agroforestry. Secondly, the schedule of forest management activities was based on the traditional seasonal calendar (Pranatamangsa). Thirdly, plant types were selected based on their functions, i.e., productions, conservations, and spirituals.